Management Perspectives Pertaining to Root Cause Analyses of Nunn-McCurdy Breaches, Volume 6 Contractor Motivations and Anticipating Breaches - Arena, Mark V. (RAND Corporation, 2014)
The authors explore defense contractor motivations and identify mechanisms that might more closely align those incentives with Department of Defense goals. They also analyze major defense acquisition programs to determine if it is possible to identify programs that might incur a future Nunn-McCurdy breach by reviewing a number of acquisition programs that have incurred breaches and analyzing them for common characteristics.